Impact of Psychological Distress on Quality of Life, Self-Efficacy, and Emotional Intelligence among Female Teachers Serving in Government and Private Schools - Akhlaq, Bisma; Khan, Aqeel Ahmad (Journal of Development and Social Sciences, 2025)
The core purpose of this study was to address the psychological anomalies preferably the level of psychological distress and its impact on the teacher’s quality of life, their self-efficacy and on the level of their emotional intelligence. This is an acknowledged fact that Psychological distress is a vital issue now a days prevailing among school teachers particularly among females. Persistent stress, workload, and lack of support contribute to emotional exhaustion and reduced professional effectiveness. This was a quantitative study with a cross-sectional research design. Data was collected by using the Kessler Psychological Distress Scale. Quality of life scale, Self-Efficacy scale, and emotional intelligence scale. The results revealed that the psychological distress significantly predicts each facet of the quality of life and the overall quality of life. This was also reported that psychological distress significantly and negatively predicts self-efficacy and emotional intelligence in both school types. On the basis of the findings this is suggested to the higher authorities to start prevention programmes to reduce the psychological distress of school teachers.